Revitalisasi Nilai Nilai Pendidikan Agama Islam Dalam Pembelajaran Modern: Strategi Penguatan Karakter Peserta Didik Era Digital - M. Nuzulul Ulum; M. Affan Ramadhan; Muhammad Fadhil Raihan Iryandi (Jurnal Pendidikan Agama Islam, 2026)
This study examines the revitalization of Islamic Religious Education values in modern learning as a strategy to strengthen students’ character in the digital era. Using a qualitative approach based on library research, this study reviews literature from the past five years related to the integration of Islamic values, digital literacy, curriculum innovation, and the role of teachers in shaping the character of the digital generation. The findings indicate that the transformation of Islamic Religious Education requires not only the utilization of technology, but also curriculum renewal, enhancement of teachers’ digital competencies, adaptive educational management, and the contextualization of values within students’ digital lives. The revitalization of Islamic Religious Education has been proven to strengthen students’ religiosity, digital ethics, and social responsibility when implemented holistically by involving schools, families, and the digital ecosystem. This study offers a comprehensive revitalization model as a strategic effort to build students’ character that is both morally grounded and adaptable to technological developments.